Alleviation of Poverty through Sustainable Management and Market Promotion of Medicinal and Aromatic Plants in Swat, Pakistan: Alleviation of Poverty through Sustainable Management - Sher, Hazrat; Ali, Ahmad; Ullah, Zahid; Sher, Hassan (Ethnobotany Research and Applications, 2022)
Background: District Swat, Pakistan is a potential hub of medicinal and aromatic plants (MAPs) which can substantially contribute to social, economic and cultural uplift of local communities. Therefore, the present study was conducted to explore the market potential for MAPs in the study area. Methods: Interviews were conducted with medicinal plant collectors, dealers and hakims to gather information about medicinal properties, pattern of collection and market status of MAPs in the study area. For this purpose, extensive field surveys were carried out in the study area and questionnaires were developed as a tool for interviews and data collection. Results: The study reported 58, 38 and 64 plant species at collectors’, dealers’ and hakims’ level. These plants are being used as medicines by local inhabitants to overcome their health problems and traded to subsidize low income for their basic needs. However, it was revealed that collectors had very little marketing skills and were unaware of high market value of their products, therefore, received minimum financial reward in the trade chain of medicinal plants. Increasing pressure on natural resources and decreasing trend in availability of important MAPs was also observed. Conclusion: An urgent need to investigate links between overexploitation of species and quality of herbal medicines in the global market and to develop conservation strategies for MAPs is suggested. It is also recommended to develop training programs for collectors of medicinal plants in order to improve sustainability, trade monitoring and community participation in natural resource management. Keywords: Medicinal plants, herbal market, quality trade monitoring, resource management